2019
DOI: 10.1063/1.5082244
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of crystal nucleation in entangled polymer melts under start-up shear conditions

Abstract: Understanding the flow induced crystallisation (FIC) process is necessary due to its technological relevance to polymer processing. Polymer crystallisation controls the morphology of semi-crystalline polymers and hence the properties of the end product. We perform molecular dynamics simulations of polymer melts consisting of sufficiently entangled linear chains under shear flow. We determine the Rouse relaxation time (τ R ) for linear polymer chains using an established rheological model at different temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 104 publications
2
28
0
Order By: Relevance
“…As such, polymer crystallization is being increasingly probed with in silico tools, particularly Molecular Dynamics (MD) simulations, which provide fine-grain access in both time and space to the molecular-level details of polymer crystallization (e.g., see ref. 5,6,9,10,12,13,42,43).…”
Section: 2 Sincementioning
confidence: 99%
“…As such, polymer crystallization is being increasingly probed with in silico tools, particularly Molecular Dynamics (MD) simulations, which provide fine-grain access in both time and space to the molecular-level details of polymer crystallization (e.g., see ref. 5,6,9,10,12,13,42,43).…”
Section: 2 Sincementioning
confidence: 99%
“…Recently, MD has been used to investigate the viscoelastic behavior of coarse‐grained polyethylene chains, in which C X denotes a melt of linear chains containing X carbon atoms. This system has about 75 carbon atoms per entanglement . Unentangled C50 and slightly entangled C178 chains have been simulated in bulk and in confined systems.…”
Section: Introductionmentioning
confidence: 99%
“…Unentangled C50 and slightly entangled C178 chains have been simulated in bulk and in confined systems. MD has been used to explore the structural, conformational, rheo‐optical, and topological properties of an entangled C400 chains in the linear and highly nonlinear regimes; the dynamics and rheology of supercooled melts of C10 C20 and C150, and C1000 chains; the steady and transient behavior of a C100 melt; the steady and transient behavior of a C400 melt; and steady and startup shear of a C700 melt …”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations can complement experiments. Recent simulations have resolved individual nucleation events from monodisperse chains, to quantify FIN [14][15][16][17][18][19]. Simulations of 150-carbon polyethylene [15], showed that the Kuhn segment nematic order, P 2,K , is the key parameter for FIN.…”
mentioning
confidence: 99%